Sexism and female politicians : research on newspapers' representation - Siti Aisyah Roslan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research intends to study the occurrence of sexist remarks and the representation of the media on female politicians. Mainstream newspapers from the United States, The New York Times and The Washington Post; the United Kingdom, The Guardian and The Telegraph, were used as the main samples of the research. The data analysis was divided into two different levels, latent and manifest, in which Lia Litoselliti's framework of gender-bias checklist was used as the main indicator of the occurrence of latent sexist remarks. However, throughout the research, there were other kinds of sexist remarks, hence those were classified as 'Others', for example stereotyping; spouse-mention; association with male figure; emphasizing on appearance, popularity and emotion; focusing on trivial issues; questioning credibility and lack of mentioning. Manifest analysis was done by analyzing the overall 'tone' of the news representation whether it is positive, negative, neutral or a mix of positive and negative; also by analyzing the impact of news reporting on the readers by analyzing the readers' comments and letters published in the newspapers. It is also crucial to note that, the research was initiated by a few notions which were sexist that mostly occurred on common women. First world countries are more cautious about sexism issues, hence less occurrence will be detected and journalists nowadays are more 'sensitive' and reluctant in representing females especially public figures in a sexist manner. Unfortunately, the findings have proven otherwise. In this research, it shows that sexism did not only target common women but also women in power. Even within the first world countries and despite the awareness and consciousness of the issue, high frequency of sexist remarks can still be detected. Sexism persistently takes place in society and it is just the manner it appears which is different. More indirect and tacit sexist remarks were found instead of direct and blatant sexist remarks; eventually this also answers the final notion that journalists are only more 'sensitive' and reluctant to openly and explicitly represent women especially public figures in a sexist manner, but they do it anyways subtly and implicitly. These findings answered the research questions by exploring the new style of sexist representations on female politicians.